Nasoalveolar Molding Treatment for a Patient With Amniotic Band Syndrome: A Case Report - Ozturk, Firat; Hatunoglu, Erdem; Altun, Oguzhan (Aves, 2014)
Amniotic band syndrome (ABS) is an uncommon congenital malformation characterized by clubfoot deformity, hand and finger anomalies, and cleft lip and palate. In this study, the literature about ABS-possible etiology, treatment protocols, and medical procedures-is discussed. The aim of this study was to evaluate efficiency of nasoalveolar molding therapy for a patient with cleft lip and palate and ABS. Changes were evaluated before, during, and after the treatment period using a three-dimensional surface imaging system.
Keywords: 3dMD; Amniotic band syndrome; Cleft lip and palate; Nasoalveolar molding